Effects of High-Intensity Interval Training on the Vascular and Autonomic Components of the Baroreflex at Rest in Adolescents - Oliveira, R. S.; Barker, A. R.; Kranen, S. H.; Debras, F.; Williams, C. A. (Pediatric Exercise Science, 2022)
Elevated blood pressure is positively associated with atherosclerotic progression in healthy youth (22). A mechanism underpinning the development of hypertension is an impaired cardiac baroreflex sensitivity (BRS). In adults decreased BRS at rest has been shown to predict hypertension over 5 years (5), and BRS impairment measured using spontaneous indices is also observed in adolescents with prehypertension (6,10,11). Exercise training has been shown to improve BRS in healthy adults. In this population, increases in BRS were observed after 12 weeks of high-intensity interval exercise (HIIE) training (9) but not following moderate-intensity continuous training of similar duration (7,20), indicating that the intensity of exercise may be an important determinant of BRS adaptations. However, the influence of HIIE training on BRS in adolescents is currently unknown.